Political inequality, political participation, and support for populist parties - Kim Leonie Kellermann (Constitutional Political Economy, 2021)
We theoretically investigate how political abstention among certain social groups encourages populist parties to enter the political stage, trying to absorb inactive voters. We design a two-stage game with two established parties and n voters who jointly determine a taxation policy. The electorate is divided into two groups, the advantaged and the disadvantaged. Voters' decisions on whether to participate depend on a party's tax rate proposal and on general party ideology. Effective political participation requires a certain amount of financial, social and intellectual resources to, for example, evaluate party programs or to engage in political discussion. As the disadvantaged are endowed with fewer resources, they lack political efficacy, resulting in less political participation. Consequently, the established parties propose a tax rate which is biased towards the preferences of the advantaged. The unused voter potential among the disadvantaged draws the interest of a populist challenger. To win support from the disadvantaged, the challenger party optimally proposes a respectively biased tax rate, which then works to polarize the political spectrum.Please confirm if the author names are presented accurately and in the correct sequence (given name, middle name/initial, family name). Author 1 Given name: [Kim Leonie] Last name [ Kellermann]. Also, kindly confirm the details in the metadata are correct.All correct.
Keywords: D63; D71; D72; C72; 330; Populist parties; Political participation; Political inequality; Probabilistic voting